Gorlin-Goltz Syndrome. (3rd October 2012) - Pandeshwar, Padma; Jayanthi, K.; Mahesh, D.
Abstract : The Gorlin-Goltz syndrome (GGS) (the nevoid basal cell carcinoma syndrome—NBCCS) is a rare autosomal dominant syndrome caused due to mutations in the PTCH (patched) gene found on chromosome arm 9q. The syndrome, characterized by increased predisposition to develop basal cell carcinoma and associated multiorgan anomalies, has a high level of penetrance and variable expressiveness. GGS is a multidisciplinary problem, early diagnosis of which allows introduction of secondary prophylaxis and following an appropriate treatment to delay the progress of the syndrome. The following report emphasizes the need for awareness of the diagnostic criteria of this syndrome in cases with no typical skin lesions.